Dissecting the impact of dietary fiber type on atherosclerosis in mice colonized with different gut microbial communities - Hutchison, Evan R. (2023)
Dietary fiber consumption has been linked with improved cardiometabolic health, however, human studies have reported large interindividual variations in the observed benefits. We tested whether the effects of dietary fiber on atherosclerosis are influenced by the gut microbiome. We colonized germ-free ApoE-/- mice with fecal samples from three human donors (DonA, DonB, and DonC) and fed them diets supplemented with either a mix of 5 fermentable fibers (FF) or non-fermentable cellulose control (CC) diet. We found that DonA-colonized mice had reduced atherosclerosis burden with FF feeding compared to their CC-fed counterparts, whereas the type of fiber did not affect atherosclerosis in mice colonized with microbiota from the other donors. Microbial shifts associated with FF feeding in DonA mice were characterized by higher relative abundances of butyrate-producing taxa, higher butyrate levels, and enrichment of genes involved in synthesis of B vitamins. Our results suggest that atheroprotection in response to FF is not universal and is influenced by the gut microbiome.